The Impact of Workplace Romance and Sexual Harassment towards Organizational Performance and Stability: A Literature Review - Vian Ahmad Saputra; Dimas Nugroho Dwi Seputro; Irma Kurniasari; Muhammad; Refiana Dwi Maghfiroh; Septian Sony Utomo; Nurkholish Majid (PROSENAMA, 2024)
This study explores the relationship between workplace romance and sexual harassment and their effects on organizational performance and stability. While workplace romance can enhance job satisfaction and corporate culture, it also presents challenges such as privacy invasion, gossip, and workplace disruption. Particularly, romances involving hierarchical dynamics risk favoritism, conflicts of interest, and perceptions of sexual harassment, leading to reduced employee morale and organizational trust. Sexual harassment is recognized as a serious threat to organizational well-being, causing psychological distress, decreased job satisfaction, and increased turnover intention. The study highlights the need for fairness in management practices to mitigate negative impacts and foster a respectful, inclusive work environment. The research utilized a systematic review of journal articles, focusing on the implications of workplace romance and sexual harassment across various organizational settings. Data were gathered from multiple sources, including Scopus and Google Scholar, to synthesize findings and discuss broader implications for organizational stability and performance. The study’s key findings underscore the dual nature of workplace romance, which can either positively influence organizational culture or lead to conflict and legal issues, depending on management practices. Additionally, the research emphasizes the extensive impact of sexual harassment on employee well-being and organizational dynamics, including significant legal and reputational risks. The study advocates for comprehensive organizational policies addressing workplace romance and sexual harassment, along with preventive measures to maintain a conducive work environment, uphold justice, and protect employee well-being. It concludes by recommending further research to develop standardized tools for assessing the long-term effects of these issues on organizational outcomes and to examine the role of organizational culture in shaping responses to workplace romance and harassment.